2017
DOI: 10.1016/j.coastaleng.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Morphological hysteresis in the evolution of beach profiles under sequences of wave climates - Part 1; observations

Abstract: Beach response to sea level rise is investigated experimentally with monochromatic and random waves in medium scale laboratory wave flumes. Beach profile development from initially planar profiles, and a 2/3 power law profile, exposed to wave conditions that formed barred or bermed profiles and subsequent profile development following rises in water level and the same wave conditions are presented. Experiments assess profile response to a step-change in water level as well as the influence of sediment depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 46 publications
8
79
0
Order By: Relevance
“…previous model formulations). In part 1 of this work, Baldock et al (2017) showed a significant hysteresis could occur in the beach profile behaviour at equilibrium, both in the net bulk sediment transport and the shoreline response, during decreasing wave conditions, i.e. erosion continued despite a decrease in wave height.…”
Section: Current Model Formulationmentioning
confidence: 74%
See 4 more Smart Citations
“…previous model formulations). In part 1 of this work, Baldock et al (2017) showed a significant hysteresis could occur in the beach profile behaviour at equilibrium, both in the net bulk sediment transport and the shoreline response, during decreasing wave conditions, i.e. erosion continued despite a decrease in wave height.…”
Section: Current Model Formulationmentioning
confidence: 74%
“…However, in part 1 of this work (Baldock et al, 2017), laboratory experiments demonstrated a strong hysteresis in beach profile evolution during sequences of wave conditions with increasing and then decreasing energy. Notably, after equilibrium conditions were reached during strongly erosive wave conditions, erosion continued after a reduction in forcing.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations